TRANSFORMATION OF THE ORGANIZATIONAL AND ECONOMIC MECHANISM OF RAILWAY TRANSPORT DEVELOPMENT IN THE CONDITIONS OF THE DIGITAL ECONOMY - Rashid Ilkhomovich Khakimov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article examines the transformation of the organizational and economic mechanism of railway transport development in the context of the digital economy. The study explores how digital technologies—such as big data, artificial intelligence, and automation—reshape management structures, operational efficiency, and financial models within the railway sector. Special attention is given to the integration of digital platforms, intelligent transport systems, and data-driven decision-making processes. The paper identifies key challenges, including infrastructure modernization, cybersecurity risks, and investment constraints, while highlighting opportunities for improving service quality, reducing costs, and increasing competitiveness. The results demonstrate that the transition toward a digital economy requires a comprehensive transformation of institutional frameworks, economic tools, and governance approaches in railway transport systems.